Big Data Analytics dalam Pengambilan Keputusan Akuntansi Manajerial : Study Literatur - Hairunisa Astari; Muhammad Rizal (Jurnal Ilmu Ekonomi dan Bisnis, 2025)
Digital transformation has shifted managerial accounting from historical reporting to a predictive information system. Big Data Analytics (BDA) allows organizations to process large volumes of structured and unstructured data, providing real-time and relevant insights for decision-making. This study employs a literature review of twelve national and international publications. The findings indicate that BDA improves accounting information quality, operational efficiency, strategic planning, and fraud detection. Challenges include limited infrastructure, low data literacy among accountants, and ethical or privacy issues. Effective implementation requires technological investment, human capital development, and clear regulations to ensure managerial accounting becomes more adaptive and strategic.